Tunable Magnetic Anisotropy and Dzyaloshinskii-Moriya Interaction in an Ultrathin van der Waals Fe3GeTe2/In2Se3 Heterostructure - Chen, Dong; Sun, Wei; Li, Hang; Wang, Jianli; Wang, Yuanxu (Frontiers in Physics, 2020)
The promise of future spintronic devices with nanoscale dimension, high-density and low-energy consumption motivates the search for van der Waals heterostructure that stabilize topologically protected whirling spin textures such as magnetic skyrmions and domain walls. To translate these compelling features into practical devices, a key challenge lies in achieving effective manipulation of the magnetic anisotropy energy and the Dzyaloshinskii-Moriya (DM) interaction, the two key parameters that determine skyrmions. Through the first-principles calculation, we demonstrate that the polarization-induced broken inversion symmetry in the two-dimensional Fe3GeTe2/In2Se3 multiferroic heterostructure does cause an interfacial DM interaction. The strong spin-orbit coupling triggers the magnetic anisotropy of the Fe3GeTe2/In2Se3 heterostructure. The magnetic anisotropy and the DM interaction in Fe3GeTe2 can be well controlled by the ferroelectric polarization of In2Se3. This work paves the way towards the spintronic devices based on van der Waals heterostructures.